Efectos de la anomia, alineación y confianza en la conducta antisocial en jóvenes fuera del sistema escolar y laboral. (2014)
The study aimed to establish the antisocial and criminal behavior from perceived social and psychological anomie, alienation and confidence in institutions in young people who are outside the education system and labor in Hermosillo (Sonora), Mexico. The results indicate that psychological and social anomie, alienation and confidence in institutions can explain 28% of the variability in the expression of antisocial and criminal behavior. In addition, three profiles were found that were called adolescents: a) tight, b) alienated c) deinstitutionalized: We conclude that public policies aimed at young people must build trust and seek ways to facilitate them the access to formal education systems.